A descriptive study of laparoscopic gynaecological surgery at three academic hospitals in JOHANNESBURG - Gwala, Bhekuyise Richman Antony (My University, 2018)
INTRODUCTION. Laparoscopic surgery is one of the most important diagnostic and therapeutic tools in the present surgical era. In gynaecology, almost all types of surgery can now be performed through the laparoscope, depending on the skills and experience of the surgeon and the availability of proper instrumentation. Chris Hani Baragwanath Academic Hospital (CHBAH), Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) and Rahima Moosa Mother and Child Hospital (RMMCH), are three tertiary, academic and referral hospitals in Johannesburg. These hospitals perform, on average 3600 gynaecological surgeries annually. We hypothesized that; less than 25% of gynaecological surgery is performed laparoscopically by each of the three hospitals. We set out to prove this hypothesis using data from August 2012 to July 2013. OBJECTIVES. The objectives of this study were to determine the proportion of gynaecological surgery, the clinical conditions and the types of laparoscopic gynaecological procedures which were performed from 01August 2012 to 31July 2013. METHODS. Our setting included all three hospitals. The population size was 3299 patients. The research design was descriptive, retrospective record review. Included were all the elective gynaecological surgeries as well as surgeries performed for ectopic pregnancies from 2012-2013. Elective theatre booking records, elective theatre admission records as well as theatre procedure records were retrieved to determine all the elective gynaecological surgeries performed during the study period. Ectopic pregnancy theatre records were included. The data was entered using Microsoft Excel and then exported to the STATA® software version 11 for analysis with the aid of the statistician. Descriptive statistics based on the results were done by giving summary statistics of frequencies and percentages for categorical variables, as well as mean ± standard deviation and median for continuous variables. Student’s T-test was used for parametric data and Mann-Whitney test for non-parametric data to determine frequency distribution. Statistical significance was ascertained at the 5% level. RESULTS. A total of 3979 gynaecological surgeries were performed during the study period. 680 patients were excluded. 3299 patients formed our study sample. The most common indications for surgery were ectopic pregnancies (40.7%) and fibroids (33%). 8.4% of gynaecological surgeries were performed laparoscopically. The hospital contributions were CHBAH (4.8%); CMJAH (5%) and RMMCH (17.2%). 55.1% of all laparoscopies were diagnostic; CHBAH (57.6%), CMJAH (63.8%) and RHMMCH (51.6%).The second most common type of laparoscopic surgery was sterilizations (35.8%); RHMMCH (47.2%), CHBAH (21.2%) and CMJAH (17.0%). 53.5% of the indications for laparoscopies were due to pelvic pain, CHBAH (54.6%); CMJAH (63.8%) and RMMCH (50.0%). The second most common indications for laparoscopy were sterilizations (35.5%). CONCLUSION. The study confirms our hypothesis that less than 25% of gynaecological surgeries were performed laparoscopically by each of the three tertiary hospitals. The majority of the laparoscopies were level one and the indications were pelvic pain and sterilizations. The design of the study was retrospective record review, therefore bias in patient selection for laparoscopy could not be excluded. We suspect that most of the laparoscopies performed, were for teaching purposes. There were no dedicated gynaecological endoscopy and infertility clinics. The large sample size, the long study period and the tertiary multicenter setting, are strengths of the study. We recommend a prospective multicenter study for the future.
A Research Report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirement for the degree of Master of Medicine in Obstetrics and Gynaecology, 2018